Prediction of 2D Isodose Curve on Arbitrary Field Size in Radiation Treatment Planning System (RTPS) - Nugraheni, Dewi Tri; Gunawan, Vincensius; Anam, Choirul (JURNAL SAINS DAN MATEMATIKA, 2015)
The study on prediction of 2D isodose curves for atbitrary field size has been done. Isodose curve is very useful for plannning and evaluation of doses received by patients in the radiotherapy treatment. The percentage depth dose (PDD) and dose profiles data for standard field size (square) were obtained from measurements in the Kensaras hospital, Semarang Regency. Dose profiles were taken at a depth of 1.5 cm and a radiation source to skin distance (SSD) of 100 cm. The calculation of PDD data in any field size uses linear interpolation method. While the calculation of the dose profile curve uses the widening, narrowing and weighting interpolation method. Firstly, the calculation of PDD and dose profile for standard field sizes of 3x3, 10x10, 15x15 and 20x20 cm2 were carried out and the results were compared to the measurements. Secondly, the PDD and dose profile for arbitrary field sizes 7x7 dan 13x13 cm2 were calculated. After that, the isodose curves for arbitrary field sizes were generated. The results showed that PDD curves of standard field sizes have maximum deviation values < 5% compared to the measurements. While the dose profile curves for field sizes up from 5x5 cm2 have maximum deviation values approximately 5% which was less than measurement. The profile curve of field size of 3x3 cm2 has maximum deviation value >5%. These results showed that our proposed algorithm was relatively valid. In this study, the PDD, dose profile and isodose curves of arbitrary field sizes 7x7cm2 and 13x13 cm2 were succesfully generated.